1-Adamantanamine-based triazole-appended organosilanes as chromogenic "naked-eye" and fluorogenic "turn-on" sensors for the highly selective detection of Sn2+ ions. (23rd March 2022) - Singh, Gurjaspreet; Kaur, Jashan Deep; Pawan,; Diksha,; Sushma,; Suman,; Shilpy,; Satija, Pinky; Singh, K. N.
Abstract : 1-Adamantanamine based organosilanes 4a–d have been synthesized and possessed selectivity towards Sn 2+ ions only and serve as a colorimetric/fluorimetric dual-channel probe. The turn-on fluorescence has been marked on interaction with Sn 2+ ions. Abstract : The current investigation illustrates the design and facile synthesis of the 1-adamantanamine-based organosilanes 4a–d via a click silylation approach, and they were characterized well via NMR ( 1 H and 13 C) and mass spectroscopic techniques. All the synthesized organosilanes possessed preferential selectivity towards Sn 2+ ions in the presence of other relevant ions and served as colorimetric/fluorimetric dual-channel probes. The probes have been successfully employed as "naked-eye" sensors with a visible color change in daylight from transparent white to golden yellow upon binding with Sn 2+ ions. The enhancement in fluorescence is attributed to the inhibition of the PET process upon interaction with Sn 2+ ions. Furthermore, BH plots reveal the presence of strong binding with 1 : 1 stoichiometry in the physiological pH range. Moreover, the limits of detection when using 4a–d towards Sn 2+ found in this study are far lower than the WHO guidelines for drinking water. Interestingly, the chemosensor 4a has been successfully employed for performing recovery testing of Sn 2+ in real soil samples. Owing to these enticing features, this present protocol could enormously expedite the design and development of chemosensors for the detection of Sn 2+ ions.